2005
DOI: 10.1080/00365540510027228
|View full text |Cite
|
Sign up to set email alerts
|

Intravenous ceftriaxone compared with oral doxycycline for the treatment of Lyme neuroborreliosis

Abstract: This prospective, open-label, non-randomized trial at the University Departments of Infectious Diseases in Ljubljana, Slovenia, and Göteborg, Sweden, was conducted to compare the kinetics of the cerebrospinal fluid (CSF) mononuclear cell count after 10-14 d of ceftriaxone or doxycycline for treatment of Lyme neuroborreliosis. 29 patients were treated with intravenous ceftriaxone 2 g daily in Ljubljana and 36 patients with oral doxycycline 400 mg daily in Göteborg. The study protocol included lumbar puncture be… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
52
0
3

Year Published

2007
2007
2023
2023

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 96 publications
(57 citation statements)
references
References 18 publications
2
52
0
3
Order By: Relevance
“…At least 10 studies have addressed the outcomes of treating neuroborreliosis with doxycycline. 12,14,15,[19][20][21][22]27,[33][34][35] All but two 14,34 used oral doxycycline; since blood levels achieved are comparable whether this drug is given orally or IV, data from these studies of IV doxycycline have been included. All studies were performed in Europe; most patients underwent CSF examination and were shown to have a CSF pleocytosis.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…At least 10 studies have addressed the outcomes of treating neuroborreliosis with doxycycline. 12,14,15,[19][20][21][22]27,[33][34][35] All but two 14,34 used oral doxycycline; since blood levels achieved are comparable whether this drug is given orally or IV, data from these studies of IV doxycycline have been included. All studies were performed in Europe; most patients underwent CSF examination and were shown to have a CSF pleocytosis.…”
mentioning
confidence: 99%
“…18 In each study, both regimens demonstrated comparable rates of efficacy. [19][20][21][22] Although most studies have focused on patients with Lyme meningoradiculitis, two have assessed treatment response in patients with Lyme encephalopathy, defined as objectively demonstrable cognitive abnormalities on formal mental status testing or neuropsychological testing. In the first 23 (Class III), 27 adults with Lyme encephalopathy, polyneuropathy, or both were treated with ceftriaxone, 2 g IV daily for 2 weeks.…”
mentioning
confidence: 99%
“…Patients with late manifestations can have a slower response to therapy, sometimes taking weeks or months to recover [15][16][17][18][19][20][21][22][23]. Some patients may have incomplete resolution due to irreversible damage, as can occur in facial nerve palsy with residual facial weakness.…”
Section: Post-lyme Disease Syndromementioning
confidence: 99%
“…In a study by Lauhio and co-workers [23] it was shown that three month lymecycline has a favorable effect in acute chlamydia arthritis and recently it was demonstrated that six months combination therapy of two antibiotics is efficient in chronic chlamydia arthritis [24]. Single antibiotic therapy with doxycycline in disseminated LB has shown relatively low cure rates, as has been shown in studies by Borg and colleagues [25], Orgnic and coworkers [26] as well as by Ljøstad and co-workers [27]. Thus, one possibility to achieve better cure rates could be to use a combination therapy of doxycycline and intravenous ceftriaxone, at least to the subgroup of patients with persistent symptoms after ceftriaxone treatment.…”
Section: Figure 4 (A)mentioning
confidence: 92%